KONSEP DIRI PEREMPUAN PECINTA OTOMOTIF di PEKANBARU (Studi pada Komunitas Honda Brio Community) - Yuli, Resti Rohma; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The phenomenon of the female who undergoing the activities outside domestic realm is still become interesting topic.The aim of this research is to find out the background, motivation and self-concept of the female members of honda brio community. The researcher used descriptive qualitative approach by interviewing 7 participants with purposive sampling technique. The researcher used Maslow theory about the hierarchy of human needs, but in the analysis, the phenomena of elements of physiological needs are not found because of the reasons why the subject affiliate in honda brio community is caused by another need of hierarchy as follows: first, the need of sense of secure. All of the subject in this case they are all female stated that the reason why they affiliate with the community is to find out the sense of secure from other members. Second, the sense of the kinship. They affiliate with the community to build the interaction with other members like their family. Third, this research found that owning and knowing about a car and affiliating in a community become a symbol of existence and determine the social prestige that can not be denied by the subject. Meanwhile, their self-concept as the member of the community can bee seen from two cases. First, before the subject affiliate with the community, their knowledge about automotive are limited. After they affiliate with the community, they have so much more knowledge about automotive. Second, the subject hope that when they affiliate with honda brio community they become more interactive, having more knowledge and experiences and they may have a solid social community.. Â Keywords: Honda Brio Community, Self-Image, Woman.Â